Scoliosis With Concurrent Thoracic Diastematomyelia, Syrinx, and Intradural Intramedullary Epidermoid Cyst: Case Report - (:unkn) unknown (LIPPINCOTT WILLIAMS & WILKINS, 2012)
The aim of this paper is to report the first presentation of type 2 thoracic diastematomyelia with concurrent syrinx, intradural intramedullary epidermoid cyst, and scoliosis, in which scoliosis correction was performed. The incidence of intraspinal anomalies in patients with congenital spinal deformity varies from 4.9% to 58% depending on the reports by the authors and diagnostic techniques. Most of these are tethered cord, diastematomyelia, and syringomyelia. Intramedullary epidermoid cysts of the spinal cord are very rare tumors, especially those associated with spinal dysraphism. Clinical manifestations of these anomalies may be absent at first; therefore, MRI is important at initial evaluation. Intervention for intraspinal anomaly and scoliosis correction can be performed separately or together as 1 procedure. A 12-year-old girl was brought to us because of progressive spinal deformity. The patient had a right thoracic curve at T5-T12 of 31 degrees. The curve was rigid and partial fusion at T6-T8 was noted. MRI of the spinal cord was taken to detect any neural axis abnormalities, and it revealed diastematomyelia at T5-T8 levels and adjacent syringomyelia superiorly. Neurological examination was normal. The patient underwent syrinx drainage and diastematomyelia resection together with scoliosis correction in 1 surgical procedure. A white-gray-colored tissue of 1 cm diameter and well-defined borders was detected in the syrinx cavity, and it was excised. There were no intraoperative or postoperative complications. The patient began ambulating on postoperative day 2. Postoperative Cobb angle was 5 degrees and the pathologic diagnosis of the lesion was an epidermoid cyst.
Keywords: diastematomyelia; syrinx; epidermoid cyst; scoliosis; OCCULT INTRASPINAL ANOMALIES; SPINAL-CORD TUMOR; ADULT; TERATOMA